2018
DOI: 10.3390/su10020465
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Training Programs and Quality Orientation of Employees: Does Employees’ Loyalty Matter?

Abstract: Transformational training programs, employee loyalty and quality orientation of employees have been some of the important concerns for both academicians and practitioners for decades. Yet, little is known about their underlying relationship dynamics, especially in the context of higher education institutions. The pivotal aim of this study was to investigate the interplay of transformational training programs, loyalty and quality orientation of employees. For this, a causal model demonstrating the direct and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…Third, by examining the moderating effect of employee loyalty, employee loyalty as an assurance of employees' useful and positive contributions increases the performance and efforts but this study elaborates that it can also enhance negative effects. Lastly, in view of the critical role of employees' feelings for an organization [17], these results provide an insight into minimizing the occurrence of workplace ostracism to help minimize the knowledge hiding behavior and increase the organizational effectiveness. Figure 1 provides an overview of our theoretical framework.…”
Section: Introductionmentioning
confidence: 95%
“…Third, by examining the moderating effect of employee loyalty, employee loyalty as an assurance of employees' useful and positive contributions increases the performance and efforts but this study elaborates that it can also enhance negative effects. Lastly, in view of the critical role of employees' feelings for an organization [17], these results provide an insight into minimizing the occurrence of workplace ostracism to help minimize the knowledge hiding behavior and increase the organizational effectiveness. Figure 1 provides an overview of our theoretical framework.…”
Section: Introductionmentioning
confidence: 95%
“…Subsequently, [18] disclosed that training ultimately add value to organization based innovation strategies. While [4] found that transformational training programs strengthen employee loyalty. Moreover, motivation, access and benefits in regard to training have a significant effect on workers engagement [4].…”
Section: B Trainingmentioning
confidence: 99%
“…While [4] found that transformational training programs strengthen employee loyalty. Moreover, motivation, access and benefits in regard to training have a significant effect on workers engagement [4]. In general, training considered a content-based activity that a trainer targeting to transform the attitudes of workers in order to fulfil management goals [23].…”
Section: B Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems and Perspectives in Management, Volume 19, Issue 1, 2021 http://dx.doi.org/10.21511/ppm.19 (1).2021. 36 Human resource management (HRM) is considered as a central element of TQM soft dimensions (Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%